The Influence Of Risk Management On Commercial Banks' Performance In Malaysia - Hamid, Zainab Sal (2007)
The purpose of this study is to examine the relationship between bank capital, liquidity, leverage and performance of commercial banks in Malaysia during 1997 - 2006. To assess the overall performance of commercial banks, one of the risk factors highlighted by Bank Negara Malaysia was used in this research which is risk-weighted capital ratio (RWCR) as a moderator. Secondary data were used and the sources of data are gathered from Bank Negara Malaysia annual report. Regression technique was employed to test the performance of these banks. The study revealed that the commercial banks performance can be further improved with the influence of risk management practices in the bank management. Results from the analysis disclosed that RW AR which is the component of capital and RWCR were found to be significantly influenced the overall bank performance whereas CDR and DER are not significantly related. To gauge the bank soundness, risk management measures are crucial and it is imperative for banks to study their risk exposure in order to achieve strategic business objectives.